Letter from the editor (2015)
Earth Sciences Research Journal presents its latest issue, Volume 19, number 2, with a positive balance in the eve of 2016 and with the challenges for the future editions. During the last two decades, we have published more than 200 papers in all the spectrum of Earth Sciences. We expect we will be here for many years more. ESRJ is now part of international databases, and we hope to improve our numbers thanks to the tireless word we do every day for our readers. We have accomplished the principal objectives for an international publication -punctuality in our volumes, respect for the authors and the spotlight on the scientific quality. For a fair editorial process, we are part of the open access and its policies of pair blind-review. The time of the operations has been reduced, and the international participation increased. For the coming years, ESRJ would reach a better visibility thanks to the publication of top-quality scientific articles, which allows us to be part of the central positions in international databases and providing researchers with fundamental elements of their work. To make possible this goal, we want to call authors to put lights on scientific quality and editorial quality. Your help is essential for us. We want to encourage researchers to pick up ESRJ as a platform for their works, but also to check the authors' guidelines as a first step to saving efforts and time during processes. Needles to say the importance of manuscript parts, English level and images readability to the acceptation of submissions. As a complementary strategy, we would like to invite our authors to create profiles in one of the available platforms, not only as an introduction to the ESRJ editorial team but also as a promotion of your work. Several challenges we have gripped during the work of the last years, for that reason we have adopted the principles of ethic and best practices in our procedure protocols. This decision would be a tool giving papers’ authors a warranty of complete respect for their work and to readers a quality signature that our contents have been verified for their use. In this adoption of best-practices procedures, many submitted papers have been rejected for having a not proper citation; this fault needs to be eradicated from all journals promoting scientific contents. A glimpse of the numbers of ESRJ points the international collaboration as one of the biggest challenges for the future issues. International Collaboration accounts for the articles that have been produced by researchers from several countries. It's not a call to improve the rates, but the scientific quality would be feed for the interaction of researchers facing different realities. Early 2016, ESRJ will publish a special issue with the selected papers of the International Conference on Earth and Environmental Sciences by the University Malaya. This special issue on Frontiers in Earth Sciences will publish articles on the most outstanding discoveries across a broad research spectrum in the field. The mission of Frontiers in Earth Sciences is to provide an introduction to some of the current advanced concepts, problems, and controversies that are at the forefront of Earth Sciences and to obtain a view of how the different parts of the Earth behave and interact. As it has been a costume in this letter from the editor, the following paragraphs will introduce the works of the current issue. Our first paper deals with the problem of recovering Moho surface from satellite gradiometry data considering the non-isostatic corrections. The second manuscript presents a case study on the application of electromagnetic and GPR measurements to a suspicious metal-contaminated site. While subsurface pollution is very harmful to nature-beings and finally human, detection of its extent in surface and more in depth is considerably challenging. The following work analyzes the Earthquake light phenomenon based in the Christchurch earthquakes occurred in 2010 and 2011, with testimonies related from people who observed or recorded the lights. In the seismotectonic field is presented a paper showing the Strain rate in the North Anatolian Fault Zone (NAFZ), that is one of the most important fault zones of Turkey. Another Turkish submission tried to determine seismic specifications of the Bitlis province in Lake Van basin and used probabilistic seismic hazard analysis for the determination of local site-specific spectra. Also from Turkey, a paper examines the performance of a single base RTK station compared with similar systems and presenting a complete exposure of values and challenges of the system. A contribution from Iran analyzes the magmatic evolution and compositional characteristics of tertiary volcanic rocks associated with the manganese mineralization in a mine located in Central Iran. Also from in Iran, a paper assesses the stability of the rock slopes with various rock mass qualities. The manuscript discusses the combination of RMR and SMR systems to evaluate rock slope stability. From Latin America, a paper makes a contribution to the knowledge of the Tatui Formation, in Brazil, emphasized in Paleontology and Paleoenvironmental considerations. We hope you find useful these contents. Carlos VargasEditor in Chief,Earth Sciences Research Journal